Child and adolescent psychiatry - Thom, Robyn P.; McDougle, Christopher J. (New York, NY : Oxford University Press, 2021)
Part of the'What Do I Do Now? Psychiatry' series,'Child and Adolescent Psychiatry' provides a practical biopsychosocial approach to assessing and treating psychiatric disorders in children and adolescents through a series of case studies.
Also issued in print: 2021.
Includes bibliographical references and index.
Specialized.
Description based on online resource; title from home page (viewed on June 17, 2021).
Keywords: Child psychiatry; Adolescent psychiatry